Numerical Analysis of Splitting Tensile Strength of Steel Fibre Reinforced Concrete under Static Loading - Nik Hasni, Nik Ahmad Hilmi; Alisibramulisi, Anizahyati; Hassan, Rohana; Saari, Nadiah; Krishnamoorthy, Renga Rao; Adnan, Suraya Hani (Journal of Advanced Industrial Technology and Application, 2022)
This paper presents the study on the numerical analysis of splitting tensile strength test of steel fibre reinforced concrete under static loading. ABAQUS FEM software is used to model the test configuration for plain concrete and steel fibre reinforced concrete (SFRC) based on the experimental investigations that studied the effectiveness of adding steel fibres of 1.5% volume fraction into the concrete mix. Four 3D models are created which are brick concrete, brick SFRC, stone concrete and stone SFRC. The numerical analysis results are compared with the published experimental results in terms of splitting tensile strength, tensile stress-strain relationship and tensile damage. The splitting tensile strengths from horizontal stress output are found to be slightly lower compared to the experimental results with percentage difference of less than 15%. While the results from using analytical formula also underestimate the splitting tensile strength with percentage difference up to 22% when compared to the experimental results. Elastic modulus from tensile experimental results should be taken as Young’s modulus of the model since it gives results that are closer to experimental results. The Poisson’s ratio that gives the closest results to the experimental result is taken as the Poisson’s ratio of the concrete and SFRC. The adopted 3D model captured reasonably well the reaction of the concrete cylinders subjected to splitting tensile test. Numerical analysis displays a strong correlation with the experimental results after proper evaluations and realistic optimizations of the governing parameters through extensive analyses.